PERGESERAN MAKNA DALAM BERITA MOTOGP DI MEDIA DARING - Raja Saleh (tuahtalino, 2019)
This research is focused on meaning shift in MotoGP news on bola.com online media. The purpose of this study is to identify the meaning shift and types of the shift found on the online media. The data were collected by note method about 2018 MotoGP race especially from September 3 to 17, 2018. The data were analyzed by descriptive qualitative in the following steps: 1) identifying words in which the meaning was shifted, 2) classifying data into six types of shift of meaning, 3) interpreting and explaining the shift of meaning. The research findings reveal that the meaning of 25 words in MotoGP news on bola.com from September 3 to 15 2018 was shifted. 11 of them underwent the extension of meaning, 2 words underwent narrowing of meaning, 2 words underwent amelioration or becoming better interpretation of meaning, 1 words underwent a worsening interpretation of meaning, 1 words underwent synesthesia, and 8 words underwent the association. The factors that cause to the shift meaning of the MotoGP news at bola.com is the development of science and technology, social and cultural developments, associations, the development of fields of use, and the exchange of sensory responses.